The Indonesian military response to reform in democratic transition: a comperative analysis of three civilian regimes 1998-2004 - The Indonesian military response to reform in democratic transition (P3DI Setjen DPR RI dan Azzaa Grafika, 2011)
st,1./ws.c.1